Impact of hyperglycemia on myocardial ischemia–reperfusion susceptibility and ischemic preconditioning in hearts from rats with type 2 diabetes - Steen Buus Kristiansen; Kim Bolther Pælestik; Jacob Johnsen; Nichlas Riise Jespersen; Kasper Pryds; Marie Vognstoft Hjortbak; Rebekka Vibjerg Jensen; Hans Erik Bøtker (Cardiovascular Diabetology, 2019)
Abstract Background The mechanisms underlying increased mortality in patients with diabetes and admission hyperglycemia after an acute coronary syndrome may involve reduced capacity for cardioprotection. We investigated the impact of hyperglycemia on exogenously activated cardioprotection by ischemic preconditioning (IPC) in hearts from rats with type 2 diabetes mellitus (T2DM) that were endogenously cardioprotected by an inherent mechanism, and the involvement of myocardial glucose uptake (MGU) and myocardial O-linked β-N-acetylglucosamine (O-GlcNAc). Methods and results In isolated, perfused rat hearts subjected to ischemia–reperfusion, infarct size (IS) was overall larger during hyper- ([Glucose] = 22 mmol/L]) than normoglycemia ([Glucose] = 11 mmol/L]) (p < 0.001). IS was smaller in 12-week old Zucker diabetic fatty rats with recent onset T2DM (fa/fa) than in rats without T2DM (fa/+) (n = 8 in each group) both during hyperglycemia (p < 0.05) and normoglycemia (p < 0.05). IPC (2 × 5 min cycles) reduced IS during normo- (p < 0.01 for both groups) but not during hyperglycemia independently of the presence of T2DM. During hyperglycemia, an intensified IPC stimulus (4 × 5 min cycles) reduced IS only in hearts from animals with T2DM (p < 0.05). IPC increased MGU and O-GlcNAc levels during reperfusion in animals with and without T2DM at normoglycemia (MGU: p < 0.05, O-GlcNAc: p < 0.01 for both groups) but not during hyperglycemia. Intensified IPC at hyperglycemia increased MGU (p < 0.05) and O-GlcNAc levels (p < 0.05) only in hearts from animals with T2DM. Conclusion While the effect of IPC is reduced during hyperglycemia in rats without T2DM, endogenous cardioprotection in animals with T2DM is not influenced by hyperglycemia and the capacity for exogenous cardioprotection by IPC is preserved. MGU and O-GlcNAc levels are increased by exogenously induced cardioprotection by IPC but not by endogenous cardioprotection in animals with T2DM reflecting different underlying mechanisms by exogenous and endogenous cardioprotection.